2014
DOI: 10.1111/anae.12859
|View full text |Cite|
|
Sign up to set email alerts
|

Introduction of an algorithm for ROTEM-guided fibrinogen concentrate administration in major obstetric haemorrhage

Abstract: SummaryWe compared blood component requirements during major obstetric haemorrhage, following the introduction of fibrinogen concentrate. A prospective study of transfusion requirements and patient outcomes was performed for 12 months to evaluate the major obstetric haemorrhage pathway using shock packs (Shock Pack phase). The study was repeated after the pathway was amended to include fibrinogen concentrate (Fibrinogen phase).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
162
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(184 citation statements)
references
References 33 publications
11
162
4
1
Order By: Relevance
“…We thank Dr Ralph for her interest in our work [1]. We have used intra-operative cell salvage during operative obstetric interventions since 2006, and as routine practice since 2010.…”
Section: A Replymentioning
confidence: 99%
See 3 more Smart Citations
“…We thank Dr Ralph for her interest in our work [1]. We have used intra-operative cell salvage during operative obstetric interventions since 2006, and as routine practice since 2010.…”
Section: A Replymentioning
confidence: 99%
“…WO2014109659 A1). Positioning the load cell within the handle allows a disposable laryngoscope blade to be used [1]. Unlike previously used spot force sensors [1], the load cell response is linear, reproducible and measures the peak and total forces transmitted to the patient during laryngoscopy.…”
Section: Sensing the Force During Laryngoscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Results of two studies in which thromboelastography was used for management of PPH showed that functional fibrinogen deficiency could worsen the outcome of major PPH (9,10). If fibrinogen therapy is guided by results of ROTEM (Rotational thromboelastography), it will lead to reduced requirements for blood components and lower risk of circulatory overload (11). European society of anesthesiologists recommended an initial fibrinogen concentrate dose of 20-25 mL/kg in plasma fibrinogen concentration of less than 1.5-2 g/L or thromboelastography signs of functional fibrinogen deficit (12).…”
mentioning
confidence: 99%